A Case Study to Explore Influence of Traceability Factors on Australian Food Supply Chain Performance - Narsimhalu, U.; Potdar, Vidyasagar; Kaur, Arshinder (Elsevler, 2015)
Traceability in food supply chain has been an area of interest due to the challenges associated the nature of the food supply chain with short code date, high safety and risk associated with quality. With the introduction of EU Regulation 178/2002 to have mandatory traceability for food supply without defined structure of product or process to be traced makes the level of traceability a vulnerable aspect across the supply chain. The level of traceability is strongly associated with the resources required to trace & track and the supplier buyer relationship, which would help to implement an effective traceability systemThe objective of the study is to understand the interrelationship between the level of traceability (breadth, depth and quality of information) and the resources required (technology,financial and human) in achieving the given level of traceability and contribution of supplier-buyer relationship on the supply chain traceability performance using a case study based approach. The study shows as the dairy products are split into individual unit for the retail stores and not associating the batch number to the product movement from the distribution center to the retailers would create the critical traceability uniform tracking and tracing system would help in efficiency gain by reducing the product receiving time approximately from 4 hours to 20 minutes, which can reduce in humanly efforts at this stage and may help in achieving huge cost savings.